Ghrelin receptor antagonist JMV2959 blunts cocaine and oxycodone drug-seeking, but not self-administration, in male rats - Merritt, Christina R.; Garcia, Erik J.; Brehm, Victoria D.; Fox, Robert G.; Moeller, F. Gerard; Anastasio, Noelle C.; Cunningham, Kathryn A. (Frontiers in Pharmacology, 2023)
The drug overdose crisis has spawned serious health consequences, including the increased incidence of substance use disorders (SUDs), conditions manifested by escalating medical and psychological impairments. While medication management is a key adjunct in SUD treatment, this crisis has crystallized the need to develop additional therapeutics to facilitate extended recovery from SUDs. The “hunger hormone” ghrelin acts by binding to the growth hormone secretagogue receptor 1α (GHS1αR) to control homeostatic and hedonic aspects of food intake and has been implicated in the mechanisms underlying SUDs. Preclinical studies indicate that GHS1αR antagonists and inverse agonists suppress reward-related signaling associated with cocaine and opioids. In the present study, we found that the GHS1αR antagonist JMV2959 was efficacious to suppress both cue-reinforced cocaine and oxycodone drug-seeking, but not cocaine or oxycodone self-administration in male Sprague-Dawley rats. These data suggest a role of the ghrelin-GHS1αR axis in mediating overlapping reward-related aspects of cocaine and oxycodone and premises the possibility that a GHS1αR antagonist may be a valuable therapeutic strategy for relapse vulnerability in SUDs.